(untitled) (Bangladesh Journal of Medical Science, 2024)
Background Attention deficit disorder refers to a neurodevelopmental disorder that has attracted great interest in recent decades with a prevalence of about 5% of children according to the DSM V. The vision constitutes “the modality of knowledge” since this meaning, primitive, offers perceptual experiences at the origin of the development of the first cognitive acquisitions. However, the repercussions of a disorder affecting vision are significant as to the. It is therefore important to distinguish it from an intellectual development disorder. Aims and Methods This study is intended to be descriptive and analytical. It aims to highlight the attention deficit in visually impaired children enrolled in the first year of primary school. Based on 6732 children, 1761 have a vision of less than 7/10, and only 85% of them benefit from automatic refraction at the optical unit, or 1497 children. Three devices were thus used: the test of entangled figures, the observation grid and the test of the two Zazzo dams. These devices make it possible to detect deficits in the attention and concentration of visually impaired students in school in relation to the decline in their level of visual acuity. The latter leads to attentional disorders resulting in concentration defects and distractibility. This decrease in attention occurs in proportion to that of visual acuity in visually impaired children. Results & Conclusion One of the major interests in assessing attention deficit in children with visual impairments is the development of a compulsory childcare programfor pre-school child and an educational awareness plan for parents. Bangladesh Journal of Medical Science Vol. 23 No. 02 April’24 Page : 491-497